The Importance of Sex and the Meaning of Sex and Sexual Pleasure for Men Aged 60 and Older Who Engage in Heterosexual Relationships: Findings from a Qualitative Interview Study - Fileborn, B.; Hinchliff, S.; Lyons, A.; Heywood, W.; Minichiello, V.; Brown, Graham; Malta, S.; Barrett, C.; Crameri, P. (Springer New York LLC, 2017)
Â© 2017, Springer Science+Business Media New York. That many older individuals continue to engage in various forms of sexual expression well into later life is now well established in the literature. To date, however, only a small body of qualitative research has examined older menâ€™s experiences and understandings of sex in later life. Likewise, the ways in which older menâ€™s discussions on sex may be used as an avenue for â€œdoingâ€? masculinity remain underexplored. Older men are particularly interesting in this regard, as they inhabit an increasingly subordinated position in relation to hegemonic masculine ideals because of their age. To what extent might this limit or, alternatively, open up the possibilities for sexual expression and subjectivity in later life? Drawing on a subset of findings from Sex, Age, and Me: A National Study with Australian Women and Men Aged 60 and Older, data from qualitative interviews with 27 Australian men were explored in this article. The first Australian study of its kind, we argue that older men who engage in heterosexual relationships draw on a diverse and complex array of discursive positions regarding sex, relationships, and masculinity in making sense of their experiences of sex in later life. Older men are a heterogeneous group, and their experiences and understandings of sex do not simplistically follow â€œdeclineâ€? or â€œsuccessâ€? narratives of aging. The findings of this research build upon and extend emerging research illustrating the centrality of intimacy to older menâ€™s sexual lives, while simultaneously highlighting the ways in which the body and discursive constructions of sex intersect to shape older menâ€™s sexual subjectivities.